(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Urinary tract infection (UTI) is common during pregnancy and especially soin pregnant patients with diabetes mellitus. The emergence of drug resistance and particularlythe extended spectrum Beta-lactamase production by Escherechia Coli and Methicillinresistance in staphylococci, limits the choice of anti-microbials. Method: A cross-sectional study was conducted on 50 pregnant women with sign andsymptoms of UTI in the Department of Obstetrics and Gynaecology, BIRDEM generalHospital-2 from January to June 2017. The objectives of the study were to determine thepresence and type of pathogens found in pregnant diabetic women presenting with featuresof urinary tract infection, and to analyze their antibiotic sensitivity pattern. Clean catch midstreamurine samples were collected using standard procedure and culture and sensitivitywas done following standard bacteriological method. Results: Mean age of the study subjects was 29.84±5.29 yrs; 48% were in third trimester ofpregnancy; 52% had Gestational Diabetes Mellitus (GDM) and 48% had Diabetes Mellitus(DM). Out of fifty pregnant women, thirty eight (76.0%) study subjects had positive growth.Of them, Escherechia coli was found in 57.9% cases, Klebsiellain 21.1%, Staphylococcusaureus in 7.9%, Enterococcus and Pseudomonas aeruginosa each in 2.6% case. Amikacinwas found to be sensitive to 100% cases of E. Coli, Klebsiella& Enterococcus but 100%resistant to Streptococcus. Conclusion: In this study, E. Coli was the most common organisms causing UTI, which isless susceptible to conventional oral antibiotics but more susceptible to amikacin. So carefulldrug selection is required for successful outcome in UTI. Bangladesh J Obstet Gynaecol, 2018; Vol. 33(1) : 54-58